Macrophages and mast cells control the neutrophil migration induced by dentin proteins - Silva, T. A.; Lara, V. S.; Silva, J. S.; Oliveira, SHP; Butler, W. T.; Cunha, F. Q. (Int Amer Assoc Dental Researchi, 2005)
Dentin sialoprotein (DSP) and dentin phosphoprotein (DPP), the major dentin proteins, have been shown to induce neutrophil migration through release of IL-1beta, TNF-alpha, MIP-2, and KC. However, the sources of these mediators were not determined. Here, the roles of macrophages and mast cells (MC) in dentin-induced neutrophil accumulation were investigated. Peritoneal MC depletion or the enhancement of macrophage population increased DSP- and DPP-induced neutrophil extravasation. Moreover, supernatants from DSP- and DPP-stimulated macrophages caused neutrophil migration. The release of neutrophil chemotactic factor by macrophages was inhibited by dexamethasone or the supernatant of DSP- treated MC. Consistently, dexamethasone and the MC supernatant inhibited the production of IL-1beta, TNF-alpha, and MIP-2 by macrophages. This inhibitory activity of the DSP- stimulated MC was neutralized by anti-IL-4 and anti-IL-10 antibodies. These results indicate that dentin induces the release of the neutrophil chemotactic substance(s) by macrophages, which are down-modulated by MC-derived IL-4 and IL-10.
Keywords: neutrophil chemotaxis; DSP; DPP